THE ROLE AND CHALLENGES OF LECTURERS IN THE ERA OF INDUSTRIAL REVOLUTION 4.0 AND SOCIETY 5.0 IN DELIVERING LEARNING FOR MILLENNIAL STUDENTS AND GEN Z STUDENTS - Zulhawati; Meiliyah Ariani (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2023)
Higher education is one of the learning facilities for the nation's next generation which is required to produce quality human resources. The success of the educational process in higher education is influenced by many factors that are interrelated with each other. One of these factors is the lecturer. Facing the era of industrial revolution 4.0 and Society 5.0, the role of lecturers in higher education is very important and strategic. In the era of digitalization, a lecturer must be able to adapt to technological advances. This research aims to provide an overview of the role and challenges of lecturers in the industrial revolution 4.0 era in delivering learning to students in the industrial revolution 4.0 era. To prepare students to enter the world of work in the digital era. The research method used is a descriptive qualitative approach. Data collection techniques in research were carried out based on theoretical studies from searching research journals, books and papers. a descriptive qualitative approach to describe how much influence the role and challenges of lecturers in the industrial revolution 4.0 era have in delivering learning to students. The picture obtained from several literature results is that to produce graduates who have good character, lecturers must act wisely in recognizing the conditions of students and classes in this digital era. Lecturers must make changes in teaching, at least changes that start from the lecturer himself. Learning patterns can no longer use old patterns, lecturers must be able to keep up with technological developments, so as to produce highly competitive graduates. The era of industrial revolution 4.0 and society 5.0 is an era where the digital industrial world has become a paradigm and reference in the order of life, so that new literacy is needed as capital to take part in people's lives.